Impacts of Decentralization on Environmental Management in Thailand - JARUSOMBAT, SOPARATANA (Jurnal Studi Pemerintahan, 2010)
This paper describes the process, institutional and legal framework within which the envi-ronmental management operates in Thailand. It specifically focuses on the decentraliza-tion within central and local government’s role in environmental management. The meth-ods of this research use literature review. The aim of the paper is to examine how interface between the central and local loci of power have affected pieces of legislation relating tomanagement of the environment by central and local government in Thailand.